PENTINGNYA KEAMANAN DATA DAN INFORMASI DI ERA DIGITAL PADA SMK BINTANG NUSANTARA PONDOK AREN - Indra Kristianto; Muhammad Bahrein; Eka Yuni Titik Artiningsih (Abdi Jurnal Publikasi, 2025)
Based on the National Cyber ​​and Crypto Agency (BSSN) (CNN Indonesia, 2022.), in 2022 more than 700 million cyber attacks will occur in Indonesia which are dominated by ransomware or malware with the mode of asking for ransom, then web defacement attacks or hacking methods that change website content, for example changing the layout, fonts, displaying advertisements, and even changing the entire content of the website, this hacking goes further and even steals data. Information security is the protection of all types of information resources from misuse by parties. who have no authority to manage it. The aim of creating an information security system is to prevent misuse of information by parties who have no interest or have no right to manage the information. Individual data needs to be kept secure so that third parties who do not have the right to know cannot access it, whether intentionally or not (for example, a service user who overhears a conversation between two staff members about the personal lives of other service users.Information security protects sensitive information from unauthorized activities, including inspection, modification, recording and any interference or destruction.The aim is to ensure the security and privacy of important data such as customer account details, financial data, or assets. intellectual. Keywords: Security system, hacking, information